2016
DOI: 10.1155/2016/4103423
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Standardized Extract of Bacopa monnieri (Bacognize®) on Cognitive Functions of Medical Students: A Six‐Week, Randomized Placebo‐Controlled Trial

Abstract: Rationale. Bacopa monnieri, popularly known as Brahmi, has been traditionally used in Ayurveda since ages for its memory enhancing properties. However, data on placebo-controlled trial of Bacopa monnieri on intellectual sample is scarce. Hence this study was planned to evaluate the effect of Bacopa monnieri on memory of medical students for six weeks. Objective. To evaluate the efficacy of Bacopa monnieri on memory of medical students with six weeks' administration. Method and Material. This was a randomized d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 33 publications
0
35
0
3
Order By: Relevance
“…Others have studied the pharmacokinetics of bac I [42] and clinical effects of bac I, but not bac II, with no adverse effects in rats receiving 30 mg/kg orally for 6 days [43] and mice 50 mg/kg orally for 7 days [43]—5 to 8 times more bac I than the highest dose of bac I used in the present study. However, other animal studies and human clinical trials have used B. monnieri whole extract at too low a dose to be comparable to the amounts of bac I and bac II used here [44,45,46,47]. In terms of translation to human trials, based on the guidelines of the U.S. Department of Health and Human Services, Food and Drug Administration (FDA) [48], the estimation of the maximum safe starting dose in initial clinical trials is 10% of the predicted therapeutic dose, so for bac I and bac II in adults, this would be doses of 0.06 and 0.03 mg/kg, respectively, which is equivalent to approximately 4.2 mg or 2 mg, respectively, in an average 70 kg human.…”
Section: Discussionmentioning
confidence: 99%
“…Others have studied the pharmacokinetics of bac I [42] and clinical effects of bac I, but not bac II, with no adverse effects in rats receiving 30 mg/kg orally for 6 days [43] and mice 50 mg/kg orally for 7 days [43]—5 to 8 times more bac I than the highest dose of bac I used in the present study. However, other animal studies and human clinical trials have used B. monnieri whole extract at too low a dose to be comparable to the amounts of bac I and bac II used here [44,45,46,47]. In terms of translation to human trials, based on the guidelines of the U.S. Department of Health and Human Services, Food and Drug Administration (FDA) [48], the estimation of the maximum safe starting dose in initial clinical trials is 10% of the predicted therapeutic dose, so for bac I and bac II in adults, this would be doses of 0.06 and 0.03 mg/kg, respectively, which is equivalent to approximately 4.2 mg or 2 mg, respectively, in an average 70 kg human.…”
Section: Discussionmentioning
confidence: 99%
“…However, there were no results or charts pertaining to the computerized tests. Blood biochemistry also showed a significant increase in serum calcium levels (p< 0.05) (Kumar et al, 2016).…”
Section: Bacopamentioning
confidence: 92%
“…The study found statistically significant improvement in the tests relating to cognitive function after using Bacopa. These tests included various neuropsychological tests and computerized tests (Kumar et al, 2016). The neuropsychological measures for the efficiency of attention, freedom from distractibility, and working memory improved significantly with the use of Bacopa (p< 0.05) as was measured by digit span backward test.…”
Section: Bacopamentioning
confidence: 99%
“…Перші письмові згадки про застосування екстракту бакопи для лікування захворювань нервової системи, покращення пам'яті й розумових здібностей датуються 500 р. н.е. [7]. Фітохімічними дослідженнями визначено, що до складу екстракту бакопи входить понад 50 біологічно активних речовин, зокрема алкалоїди, сапоніни, стероли, глікозиди, амінокислоти [5,7,8].…”
Section: експериментальні передумовиunclassified